(3OhGeY GdhSGFd aj eWGdY GdQSGFd (B( (3aj GdejbGJ(B)s - (3YHO GdQMef Hf YeQ Hf eMeO GdGHgQjs ((3CMeO Hf YHO Gddg Hf jhSa GdeQTOi GdLRQi GdMehi s)
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GeJY Gddg HWhd HbGFg GdMeO ddg GdPi QaY GdSeGA HZjQ YeO hHYO adeG cGf Yde eG GTQfG QGLYkG Edi GdGdGJ GdJi hVYgG GdQGUOhf GdChdhf s
(3BNQgG (B:s
(3hbO PcQfG ai gPg GdebGdGJ ef GdWQb hGdeDGeQGJ eGgh cGa def JCedg ai GSJNQGL LejY GdLRFjGJ GdJi JQO Ydjg ef LejY eG GgedfG PcQg ai gPg GdebGdGJ hYdjfG Gf fNJe s
(3Cda GdeDda gPG GdcJGH ddedc CHj GdMSf GdCaVd fhQ GdOjf Ydi Hf TGgfTGg Hf CjhHs
(3jHOh CfgG cJHJ ai MjGI GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
Keywords: (3Gdadcs